SPEECH ACT ANALYSIS OF SWEAR WORDS AND TRANSLATION TECHNIQUES IN FOREST GUMP MOVIE SUBTITLES - Dewi, Dyani Masita; Lestari, Novia Diah (Universitas Gunadarma, 2023)
The aims of the study are to find out and elaborate the swearwords based on different contexts in the Forest Gump movie’s subtitle and its translation. This is to answer the questions of translation technique used in the translated subtitle, and the speech acts used in the swear words. Descriptive qualitative method is used in this research to identify and to analyse the dialogue containing swearwords in the Forest Gump movie. From the analysis, it can be seen that the most used phrase of swearword is dominated by the phrase damn it or God damn it. The speech acts found were Assertive, Directive, Expressive, and Commissive. The Source Text had the total data of speech act about 63 (sixty-three) data of which 11 data were counted as two data (2). The data comprised of Assertive, Directive, Expressive and Commissive. The Target Text had the total amount data of speech act about 50 (fifty) data, 3 (three) of which were not translated and therefore cannot be counted. The Data comprises of Assertive, Directive, Expressive, and Commissive. It is expected that future researchers can study further and deeper about the speech acts in swear words and the translation techniques.